2018
DOI: 10.3758/s13414-018-1527-6
|View full text |Cite
|
Sign up to set email alerts
|

Are two spaces better than one? The effect of spacing following periods and commas during reading

Abstract: The most recent edition of the American Psychological Association (APA) Manual states that two spaces should follow the punctuation at the end of a sentence. This is in contrast to the one-space requirement from previous editions. However, to date, there has been no empirical support for either convention. In the current study, participants performed (1) a typing task to assess spacing usage and (2) an eye-tracking experiment to assess the effect that punctuation spacing has on reading performance. Although co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Another approach to making texts more accessible for diverse and struggling readers is by adjusting the print itself. These alterations have taken the form of simple changes in letters, spacing between lines and sentences, or capitalization (Johnson, Bui, & Schmitt, 2018), or the insertion of additional spaces between phrases (Bever, Jandreau, Burwell, Kaplan, & Zaenen, 1990;Hirotani et al, 2006;Jandreau & Bever, 1992). Although a number of studies found that print modifications may support English learners' understanding of English texts (Lee, 2007;Lee & Huang, 2008;Shook, 1994;Simard, 2009), others reported that simple print modifications, such as underlined and bold letters, may have little or no effect on language learning (Leow, 1997;Overstreet, 1998).…”
Section: Prior Interventionsmentioning
confidence: 99%
“…Another approach to making texts more accessible for diverse and struggling readers is by adjusting the print itself. These alterations have taken the form of simple changes in letters, spacing between lines and sentences, or capitalization (Johnson, Bui, & Schmitt, 2018), or the insertion of additional spaces between phrases (Bever, Jandreau, Burwell, Kaplan, & Zaenen, 1990;Hirotani et al, 2006;Jandreau & Bever, 1992). Although a number of studies found that print modifications may support English learners' understanding of English texts (Lee, 2007;Lee & Huang, 2008;Shook, 1994;Simard, 2009), others reported that simple print modifications, such as underlined and bold letters, may have little or no effect on language learning (Leow, 1997;Overstreet, 1998).…”
Section: Prior Interventionsmentioning
confidence: 99%